Resources, policy, and research activities of biofuel in Indonesia: A review - Yanuandri Putrasari; Achmad Praptijanto; Widodo Budi Santoso; Ocktaeck Lim (Energy Reports, 2016)
Fossil fuels as the main energy source of every country now predicted will be ended no more than 40 years. Therefore, alternative fuel such as biofuel has been developed by many countries including Indonesia. Indonesia as one of the highest populated country and has wide areas of agriculture, forest and crop field is potential to be the highest biofuel production in the world. However, after one decade since the Government of Indonesia launched the energy Policy in 2006, appears to be interesting that the biofuels progress in Indonesia seen not well developed. One of the basic weaknesses is the program only applied to the specific area with a high biofuel resource by central government without support by local government. Furthermore, the target of biofuel programs seems to be very high or too ambitious, while the condition of the people still very traditional which can be seen from the lifestyle and their energy consumption. This paper provides in detail a review of several topics related to resource, energy consumption, policy and the research and development activities of biofuel in Indonesia. As a discussion, some recommendation provided to encourage the biofuel development in the near future.
Keywords: 330; Indonesia; Energy; Alternative fuel; Biofuel